Sakralaus ir demoniško miesto vaizdiniai lietuvių dramaturgijoje - Martišiūtė, Aušra (Literatūra, 2015)
The article explores the dramas where the city is depicted as a special place determining the dramatization of a piece of work. The city symbolism is analyzed according to the criteria of the archetypal city images formulated by M. Eliade, and J. Lotman. The first part of the article ”A sacral city – Vilnius” deals with historical dramas (“Gediminas’ Dream” by A. Fromas Gužutis, “Kęstutis’ Death” by Maironis, “Radvila the Thunder”, “The Fate of Twilight ”, and “Barbora Radvilaite” by B. Sruoga, “Živilė” by A. Škėma, “Barbora Radvilaitė” by J. Grušas, “The Cathedral” by J. Marcinkevičius, “The Crown and the Sand” by R. Samulevičius, and etc.). In Lithuanian dramaturgy, Vilnius meets all the criteria of an ideal, sacred city. In poetic dramas, Vilnius is described as a superb creation embodying the plenitude of human existence. The second part of the article “The Demonic City” deals with the dramas in which the city symbolism conveys the opposite of a sacred, ideal city – an eccentric and demonic city localized in the “outskirts” of cultural space. This aspect of the city symbolism is analyzed in separate subsections: “The Doomed City” (“The Sea Bells” by Vydūnas, and “The Shackles” by M. Pečkauskaitė), “The Profane City” (the comedy “Vain Attempts” by P. Vaičiūnas, “Julijana” by A. Škėma, “A Spring Song” by B. Sruoga, “The Mammoth Hunt” by K. Saja and etc.), “The Reflections of Identity” (“Liučė is skating” by L. S. Černiauskaitė, “A Neighbour”, “Madagascar”, and “A Close City” by M. Ivaškevičius).